2017
DOI: 10.3390/su9020281
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Effects of Vegetation Cover Degradation and Environmental Implications in a Semiarid Temperate Steppe, China

Abstract: Studying the impact of vegetation dynamics on hydrological processes is essential for environmental management to reduce ecological environment risk and develop sustainable water management strategies under global warming. This case study simulated the responses of streamflow to vegetation cover degradation under climate variations in the Xilin River Basin in a semi-arid steppe of northern China. The snowmelt and river ice melting processes in the Soil and Water Assessment Tool (SWAT) were improved to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
1
6
0
3
Order By: Relevance
“…Previous studies also indicated that overgrazing has been present in the Xilin river basin for a long time, triggering a series of ecological problems, including serious grassland degradation [23,48,55]. This was also confirmed in the BLR model, which presented a significant and positive coefficient in the fit BLR function, suggesting that higher grazing intensity led to a greater likeliness of vegetation degradation.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies also indicated that overgrazing has been present in the Xilin river basin for a long time, triggering a series of ecological problems, including serious grassland degradation [23,48,55]. This was also confirmed in the BLR model, which presented a significant and positive coefficient in the fit BLR function, suggesting that higher grazing intensity led to a greater likeliness of vegetation degradation.…”
Section: Discussionsupporting
confidence: 57%
“…The area is semi-arid and falls under Agro-Ecological Region 5; hence it has low agriculture potential (Chikodzi et al, 2013). However, the study area is of ecological importance, with vital wildlife corridors (Tchakatumba et al, 2019). Figure 1 shows the study area, highlighting the key settlements, rivers and ward boundaries in the southern part of Beitbridge District, Zimbabwe.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…This is confirmed by the participatory land-use plan regarding the Shashe study area prepared by Murwira et al (2006). Land cover such as vegetation, permanent grasslands and plantations restrains the surface runoff, hence reducing the chance of flooding (Sun et al, 2017). However, land-cover types such as buildings, roads, and informal settlements decrease the penetration capacity of the soil and increase the water runoff, which enhances flooding (Ouma and Tateishi, 2014).…”
Section: Land Use and Land Covermentioning
confidence: 99%
“…The degradation of grasslands increases evaporation rates [85,86] and surface runoff [83,87], reducing soil-water infiltration capacity [67,83,84]. This in turn reduces the effective soil water content [43] and increases soil loss due to erosion [88], leading to greater risks of degradation [89]. This process is highly relevant in semiarid regions, where plant and litter cover are scare per se.…”
Section: Water Cyclementioning
confidence: 99%